If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 18 = x + 32 Reorder the terms: 18 + 3x = x + 32 Reorder the terms: 18 + 3x = 32 + x Solving 18 + 3x = 32 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 18 + 3x + -1x = 32 + x + -1x Combine like terms: 3x + -1x = 2x 18 + 2x = 32 + x + -1x Combine like terms: x + -1x = 0 18 + 2x = 32 + 0 18 + 2x = 32 Add '-18' to each side of the equation. 18 + -18 + 2x = 32 + -18 Combine like terms: 18 + -18 = 0 0 + 2x = 32 + -18 2x = 32 + -18 Combine like terms: 32 + -18 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 5w+8-w=7w-2(w-4) | | 1-3=5-1 | | 7m-3=9m+6-m | | -85+3x=83-9x | | (5x-3)+(n+9)=24 | | X^3+13x^2=0 | | 6y+4=6y-9 | | 16(z+3)=4(z-9) | | (2x-4)(x+3)= | | 2a-4b=58 | | -a+5=5a+5 | | 3x-7=-3 | | F(5)=20x+11 | | 4x^3+8x^2+3x+6=0 | | q-rb=15a | | 2x+12i=3y+2yi | | 12p=p+24+p | | 18x^2+45x+15=-10 | | 2w+9=-3 | | 2m+5=m+4 | | sin(10x)*cos(5x)=0 | | 3(x^2-10)-3x=6(x^2-2x) | | 4(y+4)+3=39 | | (8y+13)(5y+24)=0 | | (4x+4)(8x+10)=0 | | 9=3-a | | 6h+5+h=-3 | | 2x^3-12x-32x-192=0 | | x-3=-3x-23 | | 10t-4= | | -4x+3=6x+23 | | 3x-4x=-4x-11 |